Research on Lightning Overvoltage of Oil-Gas Pipeline Caused by Lightning Strikes on Adjacent Electrical Transmission Line - Hu, Shangmao; Hu, Yuanchao; Wang, Jing; An, Yunzhu; Liu, Gang; Liu, Zhixiang; Cheng, Yan (Frontiers in Energy Research, 2022)
As natural lightning strikes on the transmission tower, lightning current will flow along grounding lines into the adjacent towers grounding grid. As lightning current dispersed from the tower grounding grid into soil, lightning overvoltage may be produced on adjacent pipelines. In this paper, the lightning current shunt characteristics in multi-tower is calculated by simulation method under different soil resistivity. Then based on the lightning current shunt characteristics, the current dispersion process among multi-tower grounding grids and the pipeline are analyzed with different soil resistivity, gap distance and lightning current amplitude. Finally, the protective effect of "drain wire" and "forced commutation" on pipeline overvoltage are compared. Simulation results show that with the increasing soil resistivity, tower grounding resistance is increased and tower shunt coefficient is decreased. Considering lightning current through the multi-tower grounding grids, pipeline overvoltage is much larger than that with single tower. Pipeline overvoltage is increased with soil resistivity and lightning current amplitude, while it is decreased with "pipeline-line" distance. Both "drain wire" method and "forced commutation" method can effectively reduce pipeline potential.